Low-level laser (light) therapy increases mitochondrial membrane potential and ATP synthesis in C2C12 myotubes with a peak response at 3-6 hours - Ferraresi, Cleber (Photochem Photobiol, 2014)
Low level laser (light) therapy has been used before exercise to increase muscle performance in both experimental animals and in humans. However uncertainty exists concerning the optimum time to apply the light before exercise. The mechanism of action is thought to be stimulation of mitochondrial respiration in muscles, and to increase adenosine triphosphate (ATP) needed to perform exercise. The goal of this study was to investigate the time course of the increases in mitochondrial membrane potential (MMP) and ATP in myotubes formed from C2C12 mouse muscle cells and exposed to light-emitting diode therapy (LEDT). LEDT employed a cluster of LEDs with 20 red (630 ± 10 nm, 25 mW) and 20 near-infrared (850 ± 10 nm, 50 mW) delivering 28 mW/cm(2) for 90 sec (2.5 J/cm(2)) with analysis at 5 min, 3 h, 6 h and 24 h post-LEDT. LEDT-6h had the highest MMP, followed by LEDT-3h, LEDT-24h, LEDT-5min and Control with significant differences. The same order (6h>3h>24h>5min>Control) was found for ATP with significant differences. A good correlation was found (r=0.89) between MMP and ATP. These data suggest an optimum time window of 3-6 h for LEDT stimulate muscle cells.